The Professional Role Of Teachers And Parents In Forming Character And Developing Students' Potential - Andi Tenri Ampa (Cita konsultindo, 2023)
Parents are the characters of the mother who gave birth to the child and the father, who is basically similar to the child in terms of honesty and behavior. Apart from that, parents play an important role in shaping the personality of young people to be personal, respectful, honest, loving, responsible, affectionate, affectionate and upholding, I will do it. An instructor's duties as a demoted instructor are to instruct, educate, instruct, coach, question, and evaluate undergraduate students. Educators must be able to distinguish the talents of each student and teach and develop them according to their abilities and interests. The main task of educators in learning is to bring students to the best exhibition according to their true abilities. Therefore, the most important thing to pay attention to is how to actually focus on the characteristics of undergraduate students and how to develop their true abilities. Underwriting quality data from various angles can be used as a reference in determining the depth and width of material to accommodate increased underwriting. With this in mind, educators thoughtfully and imaginatively work with students as media and presentation materials and learning strategies to appropriately and imaginatively adapt them to suit their development and learning styles. Must work and explore. The motivation behind this research was to explore the ways in which the role of showing professions and parents is to shape people and develop research skills